Cephalometric evaluation of adenoids, upper airway, maxilla, velum length, need ratio for determining velopharyngeal incompetency in subjects with unilateral cleft lip and palate - Avinash Gohilot; Tejashri Pradhan; Kanhoba Mahabaleshwar Keluskar (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2014)
Objectives: Children with cleft lip and palate (CLP) are seen to have reduced airway size and large adenoids, which might lead to different characteristics in the upper airway and surrounding tissues from both morphological and functional perspectives. Decrease in adenoid size and increase in need ratio in cleft patients might lead to velopharyngeal incompetency (VPI) and development of nasality in adulthood. No studies have been conducted on the Indian population with variables contributing to VPI. So the aim was to evaluate the size and position of the adenoids, upper airway, maxilla, velum length and need ratio contributing to VPI in subjects with and without unilateral cleft lip and palate (UCLP) during juvenile and adolescent stages. Materials and Methods: Cephalograms of 120 subjects with 6-17 years were taken and various linear and angular measurements were measured and data was analyzed using the unpaired t test. Results: Adenoids were significantly larger and the upper airway smaller in the juvenile and adolescent cleft group than in the non-cleft group. In the adolescent cleft group, airway was larger than that in the adolescent non-cleft group. The maxilla was small and retropositioned in juvenile and adolescent subjects as compared to non cleft cases. Length of velum was smaller and need ratio was larger in both juvenile and adolescent groups as compared to the non-cleft group, suggestive of velopharyngeal incompetence. Conclusion: Decreased Adenoids, restricted airway, small, retruded maxilla, smaller velum length and larger need ratio larger were seen in the cleft group as compared to the non-cleft group, which was suggestive of VPI.